Feline Hypertrophic Osteopathy Associated with Congenital Megaesophagus: Two Case Reports and Literature Review - ABU-SEIDA, A.M.; TORAD, F.A.; HASSAN, E.A.; ALI, K.M. (Journal of the Hellenic Veterinary Medical Society, 2020)
This report describes two cases of feline hypertrophic osteopathy (HO) associated with congenital megaesophagus (ME). The diagnosis was based upon case history, physical examination, radiography and laboratory investigations. The clinical signs of both cats included; regurgitation, weakness and reluctance to walk since birth. Physical examination revealed painful and thickened long bones, swollen joints, difficult flexion of all four limbs and normal urination, defecation, appetite as well as heart and respiratory rates. The abnormal laboratory findings were thrombocytosis, leukocytosis with lymphocytosis and monocytosis. Survey and contrast thoracic radiography showed generalizedesophageal dilatation. Radiography of appendicular skeleton revealed symmetrical and massive subperiosteal new bone formation of the affected long bones and pelvis. In conclusion, radiography of extremities is highly recommended for cats admitted with congenital ME and lameness to investigate the possibility of HO. Moreover, the HO should be listed duringthe differential diagnosis of thickened limbs in cats.